Ophioglossaceae (Psilotopsida) in Ukraine - Parnikoza, Ivan; Chernyshenko, Maria; Celka, Zbigniew (Biodiversity: Research and Conservation, 2017)
The paper considers current ranges, population dynamics, habitats, threats and conservation measures of Ophioglossaceae of the Ukrainian flora. Only one specimen of Botrychium simplex was discovered in herbarium at the begining of the 19th century. Taxonomical status of Ophioglossum azoricum in Ukraine needs additional studies. Other species of the family remain rare in Ukraine; there are only two reliable current localities of B. virginianum, and seven of B. matricariifolium. The number of B. multifidum, B. lunaria and Ophioglossum vulgatum localities have been decreasing since 1980 in comparison with the previous period, especially in the lowland part of the country. This tendency is accompanied by a very low stability of well-known populations – only some of them have been occurring from before 1980 up to modern times. Current conservation of Ophioglossaceae species in the protected areas is insufficient; it is necessary to create some new and enlarge some of the existing nature protection areas and include Botrychium simplex and Ophioglossum vulgatum in the Red Data Book of Ukraine.